Change-of direction deficit in elite young soccer players - Loturco, I.; Nimphius, S.; Kobal, R.; Bottino, A.; Zanetti, V.; Pereira, L. A.; Jeffreys, I. (German Journal of Exercise and Sport Research, 2018)
Change-of-direction (COD) ability is an essential physical component for soccer. This study examined the relationships between conventional speed-power assessments and COD performance in elite young soccer players. Twenty-five under-20 male players from the same club (age: 17.6±0.8 years, height: 178.1±6.7cm, body mass [BM]: 72.2±7.9kg) performed sprint speed tests, vertical jumps, loaded jump squats, half squats, and Zigzag COD assessments. Moreover, the COD deficit was calculated as the difference between 20-m sprint velocity and Zigzag COD test velocity. A Pearson correlation analysis was used to determine the correlations between Zigzag COD performance and COD deficit with speed and power outputs. Although no significant relationships between speed-power variables and COD ability were present, there were still strong positive correlations between traditional neuromechanical measures and COD deficit. Briefly, it seems that higher performances in speed and power tests are not necessarily related to better performances in specific COD maneuvers. Therefore, it is recommended that coaches and technical staff include specific COD drills in soccer player routines to optimize the transference from speed and power capacities to specific COD performance. Die Fähigkeit des Richtungswechsels ("change of direction" [COD]) ist eine wesentliche körperliche Komponente im Fußball. In dieser Studie wurden die Beziehungen zwischen gängigen Geschwindigkeits-Leistungs-Tests und der COD-Ausführung bei jungen Spitzenfußballern untersucht. Insgesamt 25 unter 20-jährige männliche Spieler desselben Vereins (Alter: 17,6±0,8 Jahre, Körpergröße: 178,1±6,7cm, Körpergewicht [KG]: 72,2±7,9kg) absolvierten Sprintgeschwindigkeitstests, vertikale Sprünge, Jump Squats unter Last, Half Squats und Zickzack-COD-Tests. Darüber hinaus wurde das COD-Defizit als Differenz zwischen 20-m-Sprintgeschwindigkeit und Zickzack-COD-Test-Geschwindigkeit berechnet. Mit einer Korrelationsanalyse nach Pearson wurden die Korrelationen der Zickzack-COD-Ausführung und des COD-Defizits mit den Geschwindigkeits- und Leistungsergebnissen bestimmt. Auch wenn keine signifikanten Beziehungen zwischen Geschwindigkeits-Leistungs-Variablen und der COD-Fähigkeit bestanden, gab es doch starke positive Korrelationen zwischen traditionellen neuromechanischen Maßen und dem COD-Defizit. Kurzum scheinen höhere Werte in Geschwindigkeits- und Leistungstests nicht zwangsläufig mit besseren Leistungen bei bestimmten COD-Bewegungsabläufen verbunden zu sein. Daher empfiehlt es sich für Trainer und Funktionsteams, spezifische COD-Übungen in das Trainingsprogramm von Fußballern einzubeziehen, um die Übertragung von Geschwindigkeits- und Leistungskapazitäten auf bestimmte COD-Ausführungen zu optimieren.